Formulasi Solid Lipid Nanoparticle Ceramide - Garnadi Jafar; Sasanti Tarini Darijanto; Rachmat Mauludin (Universitas Lambung Mangkurat, 2015)
ABSTRAK Ceramide merupakan senyawa golongan Phytosphingosine yang secara alami terdapat didalam kulit disekitar stratum korneum yang memiliki efek sebagai menjaga kelembaban kulit. Ceramide yang terdapat dikulit secara alami akan berkurang seiring dengan penuaan dan faktor lainnya yang mengakibatkan kulit menjadi kering. Untuk mengatasi masalah ini maka pada penelitian ini dilakukan pengembangan formula solid lipid nanoparticle (SLN) ceramide sintetik yang diinkorporasikan kedalam sediaan gel agar membentuk sistem oklusif pada kulit untuk membantu dalam mengatasi TEWL (Transepidermal Water Loss). Pembuatan SLN yang digunakan yaitu ultraturax dan ultrasonik probe dengan pemilihan 3 jenis lipid padat (asam stearat, gliserol monostearat dan apifil) serta 2 jenis surfaktan (tego care dan planta care). Karakterisasi SLN meliputi analisis ukuran partikel, indeks polidispersitas, zeta potensial, morfologi (TEM) dan stabilitas fisik. SLN ceramide yang stabil terbentuk dengan kapasitas pemuatan ceramide 4 % dengan kapasitas apifil 4 % dan planta care 1 % memiliki diameter globul 113.5 ± 3.60 nm dan indeks polidisperitas 0.263 ± 0.01. Selama penyimpanan 2 bulan kandungan ceramide relative stabil dengan nilai 92.26 %. Kata Kunci : ceramide, SLN, kelembaban. ABSTRACTCeramide is a substance from Phytosphingosine group that naturally occured around stratum corneum region within our skin, possessing skin moisturizing activity. Along with aging process, ceramide will progressively reduce in number, bringing dryness to the skin. In this research, solid lipid nanoparticle (SLN) formulation containing synthetic ceramide was developed and later incorporated into gel and cream dosage forms that formed occlussive system on skin surface to reduce Transepidermal Water Loss (TEWL). SLN manufactured by ultrathurax and probe ultrasonic using 3 types of solid lipids (stearic acid, glycerol monostearate, and apiphyl) and 2 types of surfactants (tego care and planta care). SLN characterisation including particle size analysis, polydispersity index, zeta potensial determination, morphology (TEM), and physical stability. Ceramide SLN then incorporated into gel or cream dosage form. Physical stability conducted were organoleptic, pH, and viscosity tests in room temperature storage and also in accelerated stability test condition. Cream dosage forms before and after stability test (freeze-thaw instability test) were compared, showing viscosity reduction after 5cycles. Moisturity test was later conducted using CM 825 corneometer. Stable ceramide SLN was formed with 4 % ceramide loading capacity using 4 % apiphyl and 1 % planta care, having globules diameter of 113.5 ± 3.60 nm and polydispersity index of 0.263 ± 0.01. During 2 months storage, ceramide was relatively stable with concentration of 92.26 %.Keywords : ceramide, SLN, gel, cream, moisturity